2015
DOI: 10.1371/journal.pone.0141105
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Pharmacist: A Platform for Pharmacogenomics

Abstract: We present Virtual Pharmacist, a web-based platform that takes common types of high-throughput data, namely microarray SNP genotyping data, FASTQ and Variant Call Format (VCF) files as inputs, and reports potential drug responses in terms of efficacy, dosage and toxicity at one glance. Batch submission facilitates multivariate analysis or data mining of targeted groups. Individual analysis consists of a report that is readily comprehensible to patients and practioners who have basic knowledge in pharmacology, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…There is large variability among studies investigating the genetics of CIO with respect to phenotype definitions, treatment protocols, and patient demographics (29). Furthermore, examination of clinically relevant pharmacogenetic variants and drug-gene interaction networks has reported that cisplatin traits are affected by multiple genetic variations (30), providing further evidence for the polygenic nature of CIO (7). If CIO pharmacogenomic variants are to impact the lives of patients, future research will need to focus on uncovering the factors that contribute to differences and similarities in genetic susceptibility across cohorts of patients.…”
Section: Discussionmentioning
confidence: 99%
“…There is large variability among studies investigating the genetics of CIO with respect to phenotype definitions, treatment protocols, and patient demographics (29). Furthermore, examination of clinically relevant pharmacogenetic variants and drug-gene interaction networks has reported that cisplatin traits are affected by multiple genetic variations (30), providing further evidence for the polygenic nature of CIO (7). If CIO pharmacogenomic variants are to impact the lives of patients, future research will need to focus on uncovering the factors that contribute to differences and similarities in genetic susceptibility across cohorts of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our results offer an initial insight to the use of a genomic approach in pharmacogenetics showing that the advent of next generation sequencing may offer an alternative to identify and utilize individual variation to potentially explain a pharmacological relevant phenotype (Cheng et al, 2015 ). Future endeavors should focus on confirming these observations in a larger population.…”
Section: Discussionmentioning
confidence: 91%
“…Further research should involve appropriate replication studies, considering the factors discussed above regarding interstudy heterogeneity, to confirm consistent associations with specific polymorphisms to eventually influence clinical decisions. 24,64,79,86 Research via GWAS and next-generation sequencing is needed to look into the polygenic nature of PBC-induced ototoxicity 12,25,40,87 to identify additional variants and evaluate cumulative risk scores. 4,34 Lastly, increasing the diversity of populations studied will improve the curation of associated variants and improve the relevance of genomic medicine to additional populations worldwide, 88 with the eventual goal of identifying patients at high risk of ototoxicity who will benefit from less ototoxic chemotherapy regimens or the use of novel otoprotective agents.…”
Section: Future Researchmentioning
confidence: 99%